(untitled) (Altre Modernità, 2009)
This essays looks at Sorry Meniscus Excursions to the Millennium Dome (Profile Books, 1999), by I Sinclair. The book collects two ";;Expeditions to the building site on Bugsby’s Marshes";;, made in 1997 and 1999 and commissioned by the London Review of Books. The two resulting essays were published first separately, on the review, and then in a volume by Profile Books. The booklet is a curious meditation on the metropolis that is the sinclairian life-project, and it focuses on the most recent urban enterprise that can be labelled as an experiment in selling fake history for a fake political credit, giving voice to a fraud born and thriving in the fairyland of Blair’s New Labour. Sinclair’s journey also shows how any urban imagination, when applied to London, tends to become curiously self-directed: it acquires its own life, and, as the creature of Frankenstein, it claims its own right to narrate its story. Sinclair proves to be very good at listening to this story, and even better at re-narrating it, trying not to intrude too much and keeping the voice of the city as clean as possible. And in this case, it is the voice of an alien.